BE_VERWALTUNGSGERICHT 200 2014 736 vom 6. Oktober 2020 - BE Verwaltungsgericht (2020)
Klage vom 8. August 2014 (nach Vermittlungsverfahren SCHG/2013/557), Klage vom 14. Juli 2015 und Klage vom 12. Juli 2016